A brief report on combination chemotherapy and anti–programmed death (ligand) 1 treatment in small-cell lung cancer: Did we choose the optimal chemotherapy backbone?. (September 2020) - Mankor, Joanne M.; Zwierenga, Fenneke; Dumoulin, Daphne W.; Neefjes, Jacques J.C.; Aerts, Joachim G.J.V.
Abstract: Extensive-stage small-cell lung cancer (ES-SCLC) is an aggressive cancer that remains very hard to treat. The life expectancy of a patient diagnosed with this disease has not changed over the past three decades. Recently, three large clinical studies showed a survival benefit by adding an anti–programmed death (ligand) 1 (PD-(L)1 antibody to the current chemotherapy regimen. Although significant and important, the benefit seems less than what has been achieved in patients with non–small-cell lung cancer treated with chemoimmunotherapy. A number of hypotheses have been explored to explain this discrepancy. Here, we hypothesise that the current chemotherapy backbone in ES-SCLC does not contain the optimal drugs to trigger immunogenic cell death and therefore does not induce a synergy between chemotherapy and immune checkpoint inhibitor therapy. Thereby, we advocate that doxorubicin treatment instead of etoposide should be reconsidered as standard-of-care (SoC) first-line treatment of SCLC. Highlights: Chemotherapy + immunotherapy combination yielded survival in extensive-stage small-cell lung cancer (ES-SCLC). This benefit was modest, compared with what was established in other cancer types. Immunogenic cell death (ICD) is essential for chemotherapy + immunotherapy clinical responses. Chemotherapeutic agent etoposide does not induce ICD. We argue for better informed choices concerning the chemotherapy regimen combined with immunotherapy in ES-SCLC.